Undecanol-ethanol-water ternary system-based microextraction for the detection of cadmium - (:unkn) unknown (SERBIAN CHEMICAL SOC, 2019)
An eco-friendly, simple, and sensitive solidification of floating organic drop based dispersive liquid-liquid microextraction (SFODME) procedure was introduced for the separation and preconcentration of cadmium. After 2-(5-bromo-2-pyridylazo)-5-(diethylamino) phenol (5-Br-PADAP) was complexed with cadmium ions in sample, the undecanol-ethanol-water ternary system was used as an organic solvent for extraction. The main factors relevant to the microextraction efficiency such as pH, concentration of 5-Br-PADAP, amount of extraction solvent were optimized. The detection limit is 0.01 mu g L-1 along with preconcentration factor 266. The recovery of the analyte was between 98 % and 103 %, with relative standard deviation below 6 %. The developed procedure was successfully tested on the analysis of water, hair dye, and food samples.
Keywords: eco-friendly; GFAAS; microextraction; heavy metal ions; LIQUID-LIQUID MICROEXTRACTION; FLOATING ORGANIC DROP; ATOMIC-ABSORPTION-SPECTROMETRY; CLOUD POINT EXTRACTION; TRACE CADMIUM; PHASE MICROEXTRACTION; PRECONCENTRATION; SOLIDIFICATION; SEPARATION/PRECONCENTRATION; SEPARATION